Utility of Intrapartum Transabdominal Ultrasound for the Correct Placement of Vacuum during Assisted Delivery - Antonio Garcia Mejido, Jose; Borrero, Carlota; Pamela, Valdivieso; Aquise, Adriana; Serrano, Rosa; Antonio Sainz, Jose (Current Women's Health Reviews, 2014)
Objectives: To correlate the identification of fetal head position through digital examination (DE) and transabdominal ultrasound (TAU) prior to vacuum delivery. A secondary objective was to recognize how knowledge of the exact fetal head position affects the placement of the cup. Method: Women in active labor at term with normal singleton cephalic fetus were included. Transvaginal digital examination was performed and followed immediately by transabdominal ultrasound assessment. After birth, the distance between the center of the chignon and the flexion point was measured on the newborn. Results: 81 cases were included. TAU identified the fetal head position in 100% of cases and the DE in 96.3%. In 71.5% (58/81) patients DE was consistent with TAU. 100% of these cases were occiput anterior positions and 60% occiput posterior. Placing the cup in a flexing position, the lateral deviation was 0.7+/-0.5cm and the distance between the center of the chignon and the flexion point was 1.6+/-1.0cm, The center of the chignon was accurately placed at less than 2cm posterior to the flexion point in 92.5% (75/81) of the cases. Conclusions: Using DE only the vacuum cup was placed inaccurately in 1 of every 4 cases. The employment of TAU improved this result to 1 in 10.
Keywords: intrapartum